Impact Of Information Management System On Decision Making In Commercial Banks - Gobinda Prasad Acharya,; Nabin Gaire, (Journal of Contemporary Review, 2025)
The effectiveness of information systems in commercial banks is examined in this study in relation to information quality, timeliness, and reliability. A standardized questionnaire based on a five-point Likert scale was used to gather data from 120 commercial bank workers using a quantitative research approach. Descriptive analysis and Cronbach's alpha were used to verify the instrument's validity and reliability. The suggested hypotheses were tested using correlation and multiple regression analysis. The results show that information system efficacy is significantly and favourably impacted by information quality, timeliness, and reliability, with reliability appearing as the best predictor. By presenting empirical data from a developing economy's banking industry and offering useful suggestions for bank management to improve system efficacy, the paper adds to the body of knowledge on MIS.